MARTIAL ARTS: FIGHT, OR A WAY TO EDUCATION (Fiep Bulletin - online, 2015)
Although we are living in the 21st century, there are people who still do not know the essence of martial arts, or fighting styles, commonly known. The objective of this paper is to clear these doubts. To do it, we interviewed karate students' parents at the gym, and people who live in the neighborhood of Jangurussú, in Fortaleza – Ceará, place where the gym is located. It is worth to mention that the authorities consider this neighborhood as a high risk of violence. It was used a qualitative methodological procedure, using interviews that provided relevant results. At the end, it was understood that after the briefing, meetings and parents orientation, the paradigms and concepts were broken, enabling an increase of martial arts adepts.
Keywords: Martial Art. Fighting styles. Education.